Estudio geológico - geotécnico del bloque de explotación de la concesión minera “RENACER M3 CODIGO 101602”, mina “ORO SOL”, ubicada en la provincia de Azuay cantón Camilo Ponce Enríquez sector San Gerardo. - Bacuilima Tene, Edison Geovanny (2023)
In the current work, information is detailed on the topography, geology at the surface and underground level, as well as the geomechanical characteristics of the exploitation block of the "Oro sol" mine located in the Azuay province, Camilo Ponce Enríquez canton, San Gerardo sector. The work seeks as its main objective the geomechanical study of the "Oro sol” mine in order to determine its stability and thus avoid geotechnical problems such as landslides or the collapse of underground galleries among other problems, causing negative impacts to the mine and its workers, and from these results propose possible fortification or support measures, to provide stability if required in any sector within the mine. In this way, it is intended to comply with articles 41 and 134 of the “Reglamento de Seguridad y Salud en el Trabajo en el ámbito minero” which focus on planning the conditions of the rock to define the technical-mining parameters and stabilize the exploitation galleries providing adequate mining safety. To determine the geotechnics of the mine, the topography and geology of both the surface and underground were obtained, then the rock mass of the galleries of the exploitation block was characterized to proceed to give the RMR geomechanical classifications of Bieniawski, Q of Barton and GSI, and through the "Dips" and "UNWEDGE" software, the tetrahedral wedges at risk of slipping or detaching (free fall) were identified for which support measures are proposed as necessary. Keywords: Topography, geomechanical characterization, underground mining, support, exploitation block.